Etihcal and legal standards on the service of news agencies (Herald of Journalism, 2022)
The work practices and ethical standards of news agencies have not yet been fully studied and researched. From a scientific point of view, it is necessary to conduct thorough research in accordance with the current requirements, pay attention to ethical principles. Determining the expression of legal norms and ethical rules in news agencies is one of the important topics in Kazakhstani journalism.            The main purpose of the article is the scientific study of some issues of journalistic ethics in news agencies, the analysis of various codes in order to improve legal literacy, and a comprehensive study of information sources.            The scientific article describes the current activities and principles of work of various news agencies using specific examples. The features of the consumption of news agency messages and their relation to the services of the audience in Kazakhstan are analyzed. The role of ethical codes in the service of news agencies and the importance of competent work with sources are determined.            In the course of the article, the ethical standards of news agencies, the rights and obligations of journalistic creativity were considered, and an extensive study was carried out. As part of the statistical data, a survey was conducted, as well as an examination of journalistic legal norms and documents adopted at the UNESCO level. Their important role in improving journalism and creating quality content was noted.            The thematic and content nature of the articles of Kazakhstani news agencies in the legal framework, the legal signatures of journalists analyzed by the facts. The opinions and works of qualified scientists were the basis for studying the similarities and differences between Kazakhstani information resources and the principles of foreign editorial offices. A review of critical opinions on the effectiveness of ethics’s codes, based on the work of a number of theorists, presented a rational analysis, a competent conclusion and an effective idea.            In addition to the Kazinform agency, the article mentions Interfax, AFP, Associated Press and others, analyzes the work of agencies and identifies practical features. Taking into account the importance of the agency journalist's ability to establish and maintain the right relationships with sources of information, the scientific article contains facts, insights and fresh thoughts.Keywords: news agencies, codes of ethics, ethical principles, information sources.